Analysis of the Influence of Political Stability and Economic Factors on the Stock Price Index G20 Group of Countries - Nenis Tri Atikah; Zulfan Rumasoreng; Nurul Azizah Az Zakiyyah (IECON: International Economics and Business Conference, 2025)
This study has a main focus in terms of looking at the relationship between political stability and macroeconomic factors such as GDP, exchange rates, inflation, and money supply to the Stock Price Index of nine G20 member countries. This study was conducted using panel data with data sources in the form of secondary data obtained from the World Bank Indicators during the period 2011-2022. This study uses a panel data analysis method using the Fixed Effect Model which is analyzed using Eviews10. From the regression results, it was obtained that the GDP and inflation variables did not have a significant effect on the stock price index, while political stability, exchange rates, and money supply had a significant and positive effect on the stock price index. However, all the variables used simultaneously had a significant effect on the stock price index of the nine G20 member countries from the period 2011-2022.